Mining and Agricultural Colonization in the Imperial City of Southern Chile: 1551-1561 - Inostroza Cordova, Iván (Revista Complutense de Historia de América, 2013)
Study of the economic organization of the Imperial city district established since 1551 in southern Chile. We analyze the characteristics of the Spanish colonization around gold mining production, agricultural production of wheat, commercial traffic in connection with the port of Valdivia and the volume of the indigenous workforce, in the initial stage of the Spanish settlement in the region of rivers and Toltén Cautín.